The Great Expectations: Impact of One-Child Policy on Education of Girls - Wei Huang; Xiaoyan Lei; Ang Sun (Institute for the Study of Labor (IZA), 2015)
The rise in education of women relative to men is an emerging worldwide phenomenon in recent decades. This paper investigates the impact of the birth control policies on teenage girls' education attainment. The estimates suggest that the policies explain 30 percent of the education increase for women born in 1945-1980 and 50 percent of the gender gap narrowing in China. Further analysis provides some suggestive evidence for potential mechanisms, including the policy-induced expectations for labor and marriage market and subjective attitudes on children and gender-equality. These findings highlight the role of fertility policies in women's empowerment of last century.
Keywords: D84; I20; J13; J16; J18; 330; One-Child Policy; education of girls; expectation